A high throughput, high content screen for non-toxic small molecules that reduce levels of the nuclear lamina protein, Lamin B1 - Laura L. Vollmer; Fang Liu; Bruce Nmezi; Guillermo Rodriguez Bey; Nathan Herdman; Tong Ying Shun; Albert Gough; Ruiting Liu; Peter Wipf; Timothy R. Lezon; Quasar S. Padiath; Andreas Vogt (Scientific Reports)
Abstract Lamin B1 (LMNB1) is an intermediate filament protein that is an integral component of the nuclear lamina, a structure that is critical for nuclear organization and function. Mutations involving the lamin B1 gene cause the adult-onset demyelinating disorder, Autosomal Dominant Leukodystrophy (ADLD) which is charactered by increased lamin B1 expression. Increased LMNB1 expression is also associated with poorer outcomes in multiple cancer subtypes. Reducing LMNB1 is thus an attractive therapeutic pathway for ADLD and potentially other diseases. Here we present the results of a high throughput / high content screen (HTS/HCS) to identify small molecules that reduce LMNB1 levels. Approximately 97,000 molecules were screened using an inducible mouse fibroblast model of LMNB1 overexpression that we have previously generated. Two small molecules, Pubchem CID 662896 and CID 5308648, were identified that reduced LMNB1 in a dose dependent manner without causing cellular toxicity and corrected nuclear abnormalities associated with LMNB1 overexpression, a hallmark of ADLD. CID 662896 also reduced LMNB1 levels in ADLD patient fibroblast samples, exhibited favorable “drug-like” physicochemical properties and crossed the blood brain barrier in mouse studies. While CID 662896 may be a promising candidate for ADLD therapy, further investigations are required to determine its mechanism of action and ability to target disease relevant cell types.